Harga Diri, Dukungan Sosial dan Psychological Well Being Perempuan Dewasa yang Masih Lajang - Mami, Lutfita; ., Suharnan (Persona:Jurnal Psikologi Indonesia, 2015)
Abstract. The purpose of this study are examine the relationship between self-esteemand social support with the Psychological Well Being In The Still Single AdultWomen, this research method using a quantitative method with multiple regressiondata analysis techniques. Subject of the study is that single women with a number ofsubjects as many as 50 people. The results based on statistical tests show nila Fregression = 5.062; p = 0.010 <0.05. Means there is a significant relationshipbetween self-esteem and social support with psychological well beingKeywords : self esteem, social support, psychological well being